The Socio-economic Vulnerability and Villages Community Sustainability Within Tourism Development of Kepulauan Anambas Regency - Hidayat, Nur; Arifin, Hadi Susilo; Putri, Eka Intan Kumala (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Coastal and small islands identified as one of the most vulnerable region due to climate change impact. The household socio-economic vulnerability need to be capture as baseline of development. Furthermore, assessment on sustainability of coastal communities are needed as a benchmark for development goals. Aside having development challenges, archipelago ecosystem also keeps capability to shift their community from vulnerable to resilient. The sustainable development goals are:achieve sustain economic growth, social inclusive and promote sustainable natural resources management. Community based tourism development consistent with sustainable development goals. Kepulauan Anambas located in South China Sea, suitable to conduct socio-economic vulnerability and community sustainability research. The objectives are: (1) to analize socio-economic vulnerability, (2) to provide assessment on community sustainability, and (3) to determine community-based tourism development strategies. The study was located at Batu Ampar and Putik villages, Matak Island, Kepulauan Anambas regency, Indonesia. Livelihood Vulnerability Index method implemented to estimate household socio-economic vulnerability and Community Sustainability Assessment questionnaire used to generate community sustainability. SWOT analysis use to determine tourism development strategies. The results are: (1) The socio-economic vulnerability identified as Vulnerable (LVIBatu Ampar: 0,337 and LVIPutik: 0,362). (2) The village community sustainability assessment categorized as Indicates a good start toward sustainability (CSABatu Ampar: 720 and CSAPutik: 934). (3) S-O strategies (progressive/aggressive) are promote as main strategies on Community-based tourism development.